Changes in Organization of the Polish Bank System in the Years 1956—65 - Wolniak, Jerzy (Wydział Prawa i Administracji UAM, 1968)
The author considers the changes in the organization of the Polish Bank system in the years 1956—65 on the background of the decentralizing processes in the management of national economy. In existing circumstances centralization or decentralization of mangement depends primarily on the already attained level of development of national economy and also on the prospects of its further development. Decentralization of the management in national economy, after 1956 reinforced the significance if banks as links realizing the aims of the State's financial policy. This also initiated the reconstruction of the credit system, as well as numerous changes it the distribution of competency among banks. Particulary important was the transfery by the Polish National Bank to the remaining banks of a wide range of short-tenm credit, hence greatly increasing the role of these banks in the processes of creating and accumulating monetary reserves. Thus, the decentralization of the mangeimemt system contributed to the organizatiotn of a Polish banking system baaed on new principles and to the resignation of some of -the fundamental principles and forms of the banking system in Poland, before 1956. In the opinion of the author changes in the organization forms of the Polish banking system in the years 1956—65 permitted the formulation of a general thesis of the dependence of these forms in the system of management of national economy. This imeans that the organization of banks can differ, in the individual socialist countries, depending on the degree of decentralization of their mangement system.
Przemiany form organizacyjnych polskiego systemu bankowego w latach 1956—1965